Improved Volume-Of-Solid Formulations for Micro-Continuum Simulation of Mineral Dissolution at the Pore-Scale - Maes, Julien; Soulaine, Cyprien; Menke, Hannah P. (Frontiers in Earth Science, 2022)
We present two novel Volume-of-Solid (VoS) formulations for micro-continuum simulation of mineral dissolution at the pore-scale. The traditional VoS formulation (VoS-psi) uses a diffuse interface localization function psi to ensure stability and limit diffusion of the reactive surface. The main limitation of this formulation is that accuracy is strongly dependent on the choice of the localization function. Our first novel improved formulation (iVoS) uses the divergence of a reactive flux to localize the reaction at the fluid-solid interface, so no localization function is required. Our second novel formulation (VoS-psi') uses a localization function with a parameter that is fitted to ensure that the reactive surface area is conserved globally. Both novel methods are validated by comparison with experiments, numerical simulations using an interface tracking method based on the Arbitrary Eulerian Lagrangian (ALE) framework, and numerical simulations using the VoS-psi. All numerical methods are implemented in GeoChemFoam, our reactive transport toolbox and three benchmark test cases in both synthetic and real pore geometries are considered: (1) dissolution of a calcite post by acid injection in a microchannel and experimental comparison, (2) dissolution in a 2D polydisperse disc micromodel at different dissolution regimes and (3) dissolution in a Ketton carbonate rock sample and comparison to in-situ micro-CT experiments. We find that the iVoS results match accurately experimental results and simulation results obtained with the ALE method, while the VoS-psi method leads to inaccuracies that are mostly corrected by the VoS-psi formulation. In addition, the VoS methods are significantly faster than the ALE method, with a speed-up factor of between 2 and 12.